Theory of Word Formation in English and Uzbek Linguistics - Usmanova Zulaykho Ilkhombek qizi (Zien Journals, 2023)
This article provides information about the concept of word formation in the English and Uzbek languages. In addition, the theoretical views of English and Uzbek linguists on the formation of words are mentioned
Keywords: word formation; synchronic method; diachronic method